2013
DOI: 10.1002/smll.201202824
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Hollow Oxide Nanostructures: The Kirkendall Effect at the Nanoscale

Abstract: Highly ordered ultra-long oxide nanotubes are fabricated by a simple two-step strategy involving the growth of copper nanowires on nanopatterned template substrates by magnetron sputtering, followed by thermal annealing in air. The formation of such tubular nanostructures is explained according to the nanoscale Kirkendall effect. The concept of this new fabrication route is also extendable to create periodic zero-dimensional hollow nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 39 publications
3
74
0
Order By: Relevance
“…2). As expected, the surface of the obtained nanowires is smooth, which is in full agreement with our previous work [22]. We have further performed deposition of different metals (e.g., Au, Cu and Ag) and alloys (e.g., Au–Ag and Au–Cu) on substrates with large amounts of residue.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2). As expected, the surface of the obtained nanowires is smooth, which is in full agreement with our previous work [22]. We have further performed deposition of different metals (e.g., Au, Cu and Ag) and alloys (e.g., Au–Ag and Au–Cu) on substrates with large amounts of residue.…”
Section: Resultssupporting
confidence: 90%
“…1(4)). We have demonstrated in a previous work that without photoresist residues, such an approach results in nanowires with a smooth surface [22]. The formation of hillocks in the present work originates from the nodular growth taking place because of the photoresist residues acting as localized defects on the surface of the nanograted structures.…”
Section: Introductionmentioning
confidence: 56%
“…The cuprous oxide (Cu 2 O) nanotubes containing metal nanoparticles can be synthesized by thermal oxidation of copper nanowires in air using a conventional oven following two different protocols. The first protocol is the same as the one we used in our previous work and consists in inserting the samples inside the oven already heated up to 300 °C; after 3 min, the samples are immediately removed to stop the oxidation reaction. For the sake of simplicity, hereafter this protocol will be denoted as RTO for rapid thermal oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the reduced nanoobjects obtained in the previous section were thermally oxidized for 4 min using a conventional oven operating at 300 °C under ambient air. The choice of an oxidation time of 4 min was based on our previous study in which we showed that such an oxidation time is long enough to transform nanowires from solid copper into hollow Cu 2 O …”
Section: Ex Situ Oxidation Of the Reduced Nanoobjectsmentioning
confidence: 99%
“…[35][36][37] The interference lithography systems and processes used in this study were especially developed for the large-area (i.e., full wafer-scale) nanopatterning, as reported earlier. 12,[38][39][40][41][42][43] In this work, the nanopore patterns of two different periods (500 and 900 nm) were prepared by using a He-Cd laser of a wavelength of 325 nm (IK3501R-G, Kimmon Koha Co., Ltd.). After the exposure, the samples were postexposure baked on a hotplate at 100 C for 1 min.…”
Section: Methodsmentioning
confidence: 99%